Stingless bees (Hymenoptera: Apidae: Meliponini) of the Indian subcontinent: Diversity, taxonomy and current status of knowledge - Rasmussen, Claus (Zootaxa, 2013)
Eight named species of stingless bees are known from the Indian subcontinent: Lepidotrigona arcifera (Cockerell), Lisotrigona cacciae (Nurse), Lisotrigona mohandasi Jobiraj & Narendran, Tetragonula aff. laeviceps (Smith), Tetragonu-la bengalensis (Cameron), Tetragonula gressitti (Sakagami), Tetragonula iridipennis (Smith), Tetragonula praeterita (Walker), and Tetragonula ruficornis (Smith). Lectotypes are newly designated for T. bengalensis and T. ruficornis. Keys, comparative notes, and illustrations for species identification are provided. The distribution of stingless bees throughout the Indian subcontinent are summarized and concluding that they are found in most parts of the Indian subcontinent, ex-cept at higher elevation or the drier interior regions. Additional collections and studies are urgently needed to clearly de-fine the species limits of the complex “iridipennis” species group.